(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
This research explores the integration of artificial intelligence (AI) in tattoo artistry, emphasizing its application in black and grey realism through a dual-machine setup. It examines how combining AI-generated sketches with traditional artistic techniques can enhance creativity and efficiency. Additionally, the study evaluates the use of two specialized tattoo machines – one for light tones and gradients, the other for dark shades and contrasts – to achieve exceptional artistic and technical results. The study employs a multi-faceted approach, starting with AI tools such as MidJourney to generate initial sketches. These sketches are refined using digital platforms like Procreate to ensure anatomical accuracy, followed by freehand drawing to add depth and a personalized touch. During the tattoo process, a dual-machine configuration is utilized: one machine is calibrated for soft tones and smooth shading, while the other focuses on dark tones and bold contrasts, ensuring an efficient and seamless workflow. Findings reveal significant advancements in tattoo design and execution. AI accelerates the creative phase, enabling artists to conceptualize complex designs with speed and precision. These designs are tailored to complement the human form, resulting in tattoos that are cohesive and highly detailed. The dual-machine setup facilitates smoother tonal transitions, enhances realism, and improves efficiency while reducing skin trauma for faster healing. Together, AI tools and dual-machine techniques elevate artistic standards, allowing the creation of lifelike tattoos with sculptural depth The study introduces a pioneering hybrid system that merges AI-driven design processes with dual-machine tattooing methods. It seamlessly incorporates AI into tattoo workflows while showcasing a unique application technique, establishing new standards for precision and innovation in tattoo artistry. The integration of AI technology and dual-machine techniques offers significant advantages for tattoo studios. These innovations optimize workflows, minimize skin trauma, and enhance the overall quality of tattoos. By implementing this framework, studios can boost both creative development and operational efficiency, achieving superior outcomes for artists and clients alike.